Effect of tick saliva on signalling pathways activated by TLR-2 ligand and Borrelia afzelii in dendritic cells - Lieskovska, Jaroslava; Kopecky, J (Parasite immunology, 2012)
Dendritic cells are a sentinel in defending against pathogens and tick saliva facilitates transmission of tick-borne pathogens by modulating the host immune response. The maturation of dendritic cells is inhibited by tick saliva. To elucidate the mechanism of this inhibition, we tested the impact of Ixodes ricinus tick saliva on signalling pathways activated by Toll-like receptor (TLR-2) ligand and Borrelia afzelii in spleen dendritic cells. The activation of nuclear factor-κB (NF-κB) p65 and phosphatidylinositol-3 kinase (PI3K)/Akt pathways was decreased by tick saliva upon both TLR-2 and Borrelia stimulation. Among the mitogen-activated protein kinases (MAPK), the activation of extracellular matrix-regulated kinase (Erk1/2) was suppressed by tick saliva, but not p38. In response to spirochaetes, the amount of TNF-α decreased in the presence of tick saliva which was mediated by selective suppression of Erk1/2, NF-κB and Akt as tick saliva mimicked the effect of their specific inhibitors, UO126, IKK-IV and LY294002, respectively. Saliva-induced enhancement of IL-10 was not observed in the presence of specific inhibitor of Protein Kinase A (PKA), H-89, suggesting the involvement of PKA pathway in IL-10 production. Our cumulative data show that tick saliva interferes with several signalling pathways, thus modulating the immune functions of dendritic cells.
Keywords: Animals; Female; Proto-Oncogene Proteins c-akt; klíště; Toll-Like Receptor 2; Mitogen-Activated Protein Kinases; interleukin-10; ženské pohlaví; Tumor Necrosis Factor-alpha; Dendritic Cells; sliny; dendritické buňky; 1-fosfatidylinositol-3-kinasa; imunologické faktory; Borrelia burgdorferi komplex; Mice; signální transdukce; Phosphatidylinositol 3-Kinase; myši; Signal Transduction; Borrelia burgdorferi Group; Interleukin-10; protoonkogenní proteiny c-akt; transkripční faktor RelA; TNF-alfa; Immunologic Factors; toll-like receptor 2; Saliva; Transcription Factor RelA; mitogenem aktivované proteinkinasy; zvířata; Mice, Inbred C57BL; Ixodes; myši inbrední C57BL